Consumer willingness to pay a premium for orange-fleshed sweet potato puree products: a gender-responsive evidence from Becker–DeGroot–Marschak experimental auction among low- and middle-income consumers in selected regions of Nairobi, Kenya - Wangithi, Charity M.; Nyangaresi, Annette M.; Srinivasulu, Rajendran; Moyo, Mukani; Muzhingi, Tawanda; Kawarazuka, Nozomi (Frontiers in Sustainable Food Systems, 2023)
Vitamin A deficiency (VAD) is a major public health problem affecting people of all ages, particularly women of reproductive age and young children in the global South. Nutrient enriched (biofortified) orange-fleshed sweetpotato (OFSP), has promising potential, as a sustainable food vehicle, to combat VAD. Part of ongoing efforts to combat VAD, particularly amongst the urban poor populations, include introduction of innovative OFSP puree which is utilized as a functional and substitute ingredient in widely consumed baked and fried products. In Kenya, the OFSP puree is used to make commercial products that are affordable to low- and middle-income earning households. However, there is limited knowledge of consumer awareness, their willingness to pay (WTP), and if and/or how gender plays a role in the uptake of these products. Following a multistage sampling technique, this study employs the Becker–DeGroot–Marschack (BDM) experimental auction method to assess whether men and women consumers in selected highly populated low- and middle-income areas of Nairobi County in Kenya are aware and would be willing to pay for OFSP puree products. Integrating gender considerations, we use three of the most widely consumed OFSP puree products- bread, buns and chapati, three treatment categories- naive, nutritional information and OFSP puree substitute products’ references prices- to deduce the WTP for OFSP puree products among men and women. Results imply limited awareness of the existence of OFSP and OFSP puree products among men and women. However, both men and women were willing to pay a premium for the OFSP puree products. Intergender comparison showed that women were more willing to pay a premium for the OFSP puree products compared to men. Gender, age, education, knowledge of OFSP puree products, income category, availability of nutritional information and reference pricing stand out as significant determinants of WTP.